Clinical and Prognostic Impact of Copy Number Alterations and Associated Risk Profiles in a Cohort of Pediatric B-cell Precursor Acute Lymphoblastic Leukemia Cases Treated Under ICiCLe Protocol. Issue 10 (30th October 2022) - Gupta, Sanjeev Kumar; Singh, Minu; Chandrashekar, Pragna H.; Bakhshi, Sameer; Trehan, Amita; Gupta, Ritu; Thakur, Rozy; Gajendra, Smeeta; Sharma, Preity; Sreedharanunni, Sreejesh; Sachdeva, Manupdesh S.; Pushpam, Deepam; et al.
Abstract : Copy number alteration (CNA) status and CNA risk profiles of IKZF1 plus, UK-ALL CNA risk groups and MRplus scores, were evaluated for clinical and prognostic impact in a cohort of 493 B-cell acute lymphoblastic leukemia cases diagnosed and treated under the Indian Collaborative Childhood Leukemia group (ICiCLe) protocol trial. Overall CNA frequency was 59% with 60% of cases showing 2-loci deletion. CDKN2A/B deletion was most common CNA (36.3%), while IKZF1 deletion and IKZF1 plus profile were noted in 19.5% and 13.4% of cases, respectively. IKZF1 deletions and other CNA risk profiles were significantly associated with poor (PR)/high risk (HR) clinical and genetic profile parameters ( P < 0.001). In addition, the 3-year OS, event-free survival (EFS) was significantly poor with high relapse rate (RR) of 38.6%, 46.5%, and 35.2% for IKZF1 deletions, IKZF1 plus profiles, and UK-ALL CNA-intermediate risk (IR)+PR risk groups, respectively ( P < 0.001). Integrated evaluation of UK-ALL CNA risk profile with ICiCLe trial risk stratification groups revealed a worse overall survival, EFS, and RR of 63.3%, 43.2%, and 35.2% for CNA-IR+PR profile compared to CNA-good risk profile (81.3%, 65.0%, and 21.0%; P < 0.001). Hence, routine CNA testing in our setting is must to identify standard risk and IR cases likely to benefit from HR treatment.